THE TRANSFORMATION OF LEARNING MODEL BASED ON CRITICAL DIGITAL LITERACY IN HIGHER EDUCATION - Umar Manshur; Fathor Rozi (PEDAGOGIK : JURNAL PENDIDIKAN, 2025)
Low literacy and critical thinking skills remain a serious challenge to improving the quality of education in Indonesia. In the context of Islamic boarding schools (pesantren), this challenge is further complicated by the need to integrate Islamic values, the scholarly traditions of Islamic boarding schools, and the demands of 21st-century competencies. Therefore, transforming learning models that integrate critical digital literacy is an urgent need to improve the quality of learning. This study aims to analyze the transformation of critical digital literacy-based learning models in Islamic boarding schools (pesantren). The study employed a qualitative approach with a multi-site case study design. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model. The results show the development of critical digital literacy characteristics in students, including the use of digital devices, information management, digital content transformation, and socio-cultural understanding. Furthermore, the evolving learning model is adaptive, with technology integration, information exploration, collaboration, project-based learning, and a shift in the role of lecturers to facilitators. These findings confirm that critical digital literacy is not only technical but also reflective and contextual, integrated with Islamic boarding school values.